La domination incarnée. Corps et colonisation (xixe-xxe siècles) - Sophie Dulucq; Caroline Herbelin; Colette Zytnicki (Les Cahiers de Framespa)
This issue of the Cahiers de Framespa aims to offer new perspectives in a developing research field, that of bodies in imperial context. The bodies of the colonized and the colonizers – suffering, scrutinized, locked up, sexualized, gendered – have experienced power relations deep in their flesh. Through a range of specific case studies (in America, Africa and Asia), this issue provides new inquiries as well as original information on this important topic.